2018
DOI: 10.1186/s13014-018-1135-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel model to correlate hydrogel spacer placement, perirectal space creation, and rectum dosimetry in prostate stereotactic body radiotherapy

Abstract: BackgroundThe SpaceOAR hydrogel is employed to limit rectal radiation dose during prostate radiotherapy. We identified a novel parameter – the product of angle θ and hydrogel volume – to quantify hydrogel placement. This parameter predicted rectum dosimetry and acute rectal toxicity in prostate cancer patients treated with stereotactic body radiotherapy to 36.25 Gy in 5 fractions.MethodsTwenty men with low- and intermediate-risk prostate cancer underwent hydrogel placement from 2015 to 2017. Hydrogel symmetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The perirectal distance separating the prostate CTV from the anterior rectal wall following hydrogel placement was 9.6 ± 4 mm measured at the prostate midgland, at midline. The perirectal separation measured at this location has previously been shown to be predictive of rectum dosimetry [26].…”
Section: Resultsmentioning
confidence: 99%
“…The perirectal distance separating the prostate CTV from the anterior rectal wall following hydrogel placement was 9.6 ± 4 mm measured at the prostate midgland, at midline. The perirectal separation measured at this location has previously been shown to be predictive of rectum dosimetry [26].…”
Section: Resultsmentioning
confidence: 99%
“…The main limiting issues, concerning sterilization, scale-up, shelf-life, and user compliance (professional and/or patient), must be addressed before the benefits afforded by injectable hydrogels can be translated into clinical practice. Some formulations are currently in clinical trials, mainly consisting in radiopaque PEG hydrogels (TraceIT ® and SpaceOAR ® ) useful to improve the target definition of radiotherapy, thus reducing the radiation doses [299,300].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“… 8 , 12 Therefore, SpaceOAR reduced GI toxicity and helped improve bowel symptoms. 13 Additionally, several studies reported that SpaceOAR may decrease the rate of genitourinary (GU) toxicity, especially lower urinary tract symptoms (LUTS), because of the reduction of irradiation dose for the penile bulb and bladder in patients with PCa who received LDR-BT. 13 , 14 , 15 For this reason, the insertion of SpaceOAR causes anatomical changes in the pelvic organs.…”
Section: Introductionmentioning
confidence: 99%